Design and manufacture of cylindrical rings using the centrifugal casting method as an alternative to improving the quality of cast products - S. Gunara; R. Kusnowo (Dinamika Teknik Mesin, 2019)
Cylinder ring is a material for making piston rings, where the piston ring is one of the engine components that are produced by the automotive industry. At present, cylinder rings are made using the gravity casting method. But when the process of making cylindrical products using the gravity casting method, a channel system is needed so that the yield produced is so low. In addition, cast products produced by this method often have defects in the form of gas cavity defects due to the use of cores and fins caused by parting lines. This research was conducted to design and manufacture of cylinder rings using the centrifugal casting method as an alternative to improving the quality of cast products. The research process included cylinder ring design, speed experiments, cylinder ring manufacturing, visual checking before and after machining processes on Ferro Casting Ductile 500 (FCD 500) materials with a carbon composition range of 3.6-3.8%, silicon 1.8-2 , 8%, max. Manganese 0.3% and the range of pouring temperature 1350ºC-1280ºC. The results of this study proved that cylindrical ring products designed and made using the centrifual casting method with a 600 rpm motor rotational speed have no defects in the gas cavity and fins arise and produce a 95% yield.